Keynesian government spending multipliers and spillovers in the euro area - Tobias Cwik; Volker Wieland (European Central Bank (ECB), 2010)
The global financial crisis has lead to a renewed interest in discretionary fiscal stimulus. Advocates of discretionary measures emphasize that government spending can stimulate additional private spending — the Keynesian multiplier effect. Thus, we investigate whether the spending package announced by Euro area governments for 2009 and 2010 is likely to boost GDP by more than one for one. Because of modeling uncertainty, it is essential that such policy evaluations be robust to alternative modeling assumptions and parameterizations. We use five different empirical macroeconomic models with Keynesian features such as price and wage rigidities to evaluate the impact of the fiscal stimulus. Four of them suggest that the planned increase in government spending will reduce private consumption and investment significantly. Only a model that largely ignores the forward-looking behavioral response of consumers and firms implies crowding-in of private spending. We review a range of issues that may play a role in the recession of 2008-2009. Implementation lags are found to reinforce crowding-out and may even cause an initial contraction. Zero-bound effects may lead the central bank to abstain from interest rate hikes and increase the GDP impact of government spending. Crowding-in, however, requires an immediate anticipation of at least two years at the zero bound. Using a multi-country model, we find that spillovers between euro area countries are negligible or even negative, because direct demand effects are offset by the indirect effect of an euro appreciation. New-Keynesian DSGE models provide a strong case for government savings packages. Announced with sufficient lead time, spending cuts induce a significant short-run stimulus and crowding-in of private spending.
Keywords: E62; E63; H31; 330; Fiscal Policy; government spending multipliers; Model uncertainty; New-Keynesian models; Finanzpolitik; Öffentliche Ausgaben; Multiplikator; Spillover-Effekt; Keynesianismus; EU-Staaten